2015
DOI: 10.3402/tellusb.v67.26688
|View full text |Cite
|
Sign up to set email alerts
|

Methane exchange in a boreal forest estimated by gradient method

Abstract: A B S T R A C T Forests are generally considered to be net sinks of atmospheric methane (CH 4 ) because of oxidation by methanotrophic bacteria in well-aerated forests soils. However, emissions from wet forest soils, and sometimes canopy fluxes, are often neglected when quantifying the CH 4 budget of a forest. We used a modified Bowen ratio method and combined eddy covariance and gradient methods to estimate net CH 4 exchange at a boreal forest site in central Sweden. Results indicate that the site is a net so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 60 publications
(73 reference statements)
1
8
0
Order By: Relevance
“…Other studies have reported daytime minima [49,103] in CH 4 fluxes. Sundqvist, Mölder [104] measured CH 4 fluxes in the Norunda forest with different gradient methods above the canopy and suggested that the observed daytime minima could be a result of plant uptake (as previously observed from branch chamber measurements by Sundqvist, Crill [105]) and that the observed nighttime maxima could be a result of larger nighttime footprints, with distant, wetter source areas (such as the clear-cut in this study) contributing more to the measured fluxes than during daytime.…”
Section: Diel Patterns Of Ch 4 and N 2 O Fluxessupporting
confidence: 78%
“…Other studies have reported daytime minima [49,103] in CH 4 fluxes. Sundqvist, Mölder [104] measured CH 4 fluxes in the Norunda forest with different gradient methods above the canopy and suggested that the observed daytime minima could be a result of plant uptake (as previously observed from branch chamber measurements by Sundqvist, Crill [105]) and that the observed nighttime maxima could be a result of larger nighttime footprints, with distant, wetter source areas (such as the clear-cut in this study) contributing more to the measured fluxes than during daytime.…”
Section: Diel Patterns Of Ch 4 and N 2 O Fluxessupporting
confidence: 78%
“…Water table depth is a master variable that controls patterns of soil O 2 and redox potential in upland and wetland forests (Megonigal et al ., ), and strongly regulates rates of CH 4 consumption by upland soils (Topp & Pattey, ), CH 4 emission by wetland soils (Turetsky et al ., ), and CH 4 emissions by both wetland and upland tree stems (Pangala et al ., ; Terazawa et al ., ; Pitz et al ., ). Water table depth was a likely source of spatial variation in an upland boreal forest that appeared to be a net CH 4 sink when tree and soil fluxes were measured by small‐scale chambers, but a net source when measured by large‐scale micrometeorological methods (Sundqvist et al ., ). In this case, small areas of wet soils in the tower footprint may have been strong CH 4 sources.…”
Section: Trees In Forest Ch4 Budgetsmentioning
confidence: 97%
“…While chamber measurements usually found that the soil acted as a sink for atmospheric CH 4 , the latter studies have shown that boreal forests are net sources of CH 4 , contributing about 7.5% to the global CH 4 emissions (Bergamaschi et al., ; Sinha et al., ). These emissions could not be attributed to light‐dependent CH 4 production by the vegetation as no differences were observed between day and night time emissions (Bergamaschi et al., ; Sundqvist et al., ). Based on our results we hypothesize that CH 4 emissions from moss could be in part contributing to the observed CH 4 emissions in boreal forests.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, these soils were regarded to be net CH 4 sinks (Conrad, 1996;LeMer & Roger, 2001). However, quantification of CH 4 emissions (DoCarmo, Keller, Dias, DeCamargo, & Crill, 2006;Machacova et al, 2016;Sinha, Williams, Crutzen, & Lelieveld, 2007;Sundqvist, M€ older, Crill, Kljun, & Lindroth, 2015) and remote sensing methods (Frankenberg, Meirink, VanWeele, Platt, & Wagner, 2005) showed large uncertainties in CH 4 fluxes from forest ecosystems (Bergamaschi et al, 2007;Frankenberg et al, 2005), challenging the perceived role of forests as net CH 4 sinks.…”
Section: Introductionmentioning
confidence: 99%